Effectiveness, cost-utility and physiological underpinnings of the FIBROWALK multicomponent therapy in online and outdoor format in individuals with fibromyalgia: Study protocol of a randomized, controlled trial (On&Out study) - Serrat, Mayte; Ferrés, Sònia; Auer, William; Almirall, Míriam; Lluch, Enrique; D’Amico, Francesco; Maes, Michael; Lorente, Sonia; Navarrete, Jaime; Montero-Marín, Jesús; Neblett, Randy; Nijs, Jo; et al. (Frontiers in Physiology, 2022)
Introduction: The On&Out study is aimed at assessing the effectiveness, cost-utility and physiological underpinnings of the FIBROWALK multicomponent intervention conducted in two different settings: online (FIBRO-On) or outdoors (FIBRO-Out). Both interventions have proved to be efficacious in the short-term but there is no study assessing their comparative effectiveness nor their long-term effects. For the first time, this study will also evaluate the cost-utility (6-month time-horizon) and the effects on immune-inflammatory biomarkers and Brain-Derived Neurotrophic Factor (BDNF) levels of both interventions. The objectives of this 6-month, randomized, controlled trial (RCT) are (i) to examine the effectiveness and cost-utility of adding FIBRO-On or FIBRO-Out to treatment as usual (TAU) for individuals with fibromyalgia (FM); (ii) to identify pre–post differences in blood biomarker levels in the three study arms and (iii) to analyze the role of process variables as mediators of 6-month follow-up clinical outcomes. Methods and analysis: Participants will be 225 individuals with FM recruited at Vall d’Hebron University Hospital (Barcelona, Spain), randomly allocated to one of the three study arms: TAU vs TAU+FIBRO-On vs TAU+FIBRO-Out. A comprehensive assessment to collect functional impairment, pain, fatigue, depressive and anxiety symptoms, perceived stress, central sensitization, physical function, kinesiophobia, pain catastrophizing, psychological inflexibility in pain and pain knowledge will be conducted pre-intervention, at 6 weeks, post-intervention (12 weeks), and at 6-month follow-up. Changes in immune-inflammatory biomarkers [i.e., IL-6, CXCL8, IL-17A, IL-4, IL-10, and high-sensitivity C-reactive protein (hs-CRP)] and BDNF will be evaluated in 40 participants in each treatment arm (total n=120) at pre- and post-treatment. Quality of life and direct and indirect costs will be evaluated at baseline and at 6-month follow-up. Linear mixed-effects regression models using restricted maximum likelihood, mediational models and a full economic evaluation applying bootstrapping techniques, acceptability curves and sensitivity analyses will be computed. Ethics and dissemination: This study has been approved by the Ethics Committee of the Vall d’Hebron Institute of Research. The results will be actively disseminated through peer-reviewed journals, conference presentations, social media and various community engagement activities. Trial registration number NCT05377567 (clinicaltrials.gov).